2019
DOI: 10.3390/rs11030241
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Three-Dimensional Surface Motion with InSAR: Constraints from Multi-Geometry Data Fusion

Abstract: Interferometric synthetic aperture radar (InSAR) technology has been widely applied to measure Earth surface motions related to natural and anthropogenic crustal deformation phenomena. With the widespread uptake of data captured by the European Space Agency’s Sentinel-1 mission and other recently launched or planned space-borne SAR missions, the usage of the InSAR technique to detect and monitor Earth surface displacements will increase even more in the coming years. However, InSAR can only measure a one-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 164 publications
(121 citation statements)
references
References 78 publications
1
101
0
Order By: Relevance
“…Such LOS displacement rates have been converted into vertical displacement rates by neglecting horizontal velocities [12]. Fuhrmann and Garthwaite [28] have shown that the error in the vertical velocity, when converting LOS to vertical, depends on the incidence angle and the amount of horizontal motion. From a real-world local displacement phenomenon measured with Envisat data from multiple viewing geometries (four ascending and three descending passes), they found that an error of up to 67% of the maximum vertical motion was introduced into the projected vertical component when neglecting the horizontal component.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such LOS displacement rates have been converted into vertical displacement rates by neglecting horizontal velocities [12]. Fuhrmann and Garthwaite [28] have shown that the error in the vertical velocity, when converting LOS to vertical, depends on the incidence angle and the amount of horizontal motion. From a real-world local displacement phenomenon measured with Envisat data from multiple viewing geometries (four ascending and three descending passes), they found that an error of up to 67% of the maximum vertical motion was introduced into the projected vertical component when neglecting the horizontal component.…”
Section: Methodsmentioning
confidence: 99%
“…The vertical velocities were mostly over 20 mm/a and the horizontal velocities were mostly less than 5 mm/a. The maximum error resulting from the projection of LOS into the vertical velocity induced by the horizontal velocity component was [28]:…”
Section: Methodsmentioning
confidence: 99%
“…Three dimensional displacements of the ground surface are therefore mapped into a one-dimensional geometry. If InSAR data from different viewing geometries (e.g., ascending and descending orbital passes of the SAR satellite) is available, then vertical and horizontal components of displacement can be resolved (Fuhrmann and Garthwaite, 2019). Unfortunately, this is not the case for the Lake Muir earthquake, where only descending-pass Sentinel-1 SAR data is available.…”
Section: Reconciling Uav Vertical Displacement and Insar Los Displacementioning
confidence: 99%
“…The three components of the deformation vector cannot be reconstructed from a single DInSAR measurement, so various techniques were developed to overcome this limitation (Hu et al 2014;Fuhrmann and Garthwaite 2019). In rare cases (e.g., at high latitudes) 3D solution can be derived directly from three independent DInSAR observations (Gray 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, ascending and descending DInSAR data are usually acquired at different times and sometimes with different revisit fre-quencies (e.g., 24 days for RADARSAT-2 and 6 days for Sentinel-1). Fuhrmann and Garthwaite (2019) proposed to interpolate the DInSAR measurements to common epochs. The Multidimensional Small Baseline Subset (MSBAS-2D) technique was developed in order to overcome the need for interpolation.…”
Section: Introductionmentioning
confidence: 99%